PENGARUH MODERASI WORD OF MOUTH TERHADAP HUBUNGAN KEPERCAYAAN DAN KEPUTUSAN PEMBELIAN RUMAH “PARAMOUNT LAND” - Fransiscus Darren; Eddy Haryadi (Jurnal Manajemen, 2015)
This study aims to determine the effect of moderating variables Word-Of-Mouth on the relationship of Trust and Paramount Land Purchase Decision of house. The study was conducted in several clusters of housing in Gading Serpong. The sampling method used was simple random sampling. The number of samples studied were as many as 200 customers. The collected data is processed and analyzed by the IBMS SPSS 21.The results showed that there is significant influence Word of Mouth as a moderating variable on the relationship of Trust and Paramount Land house Purchase Decision. In addition, the Trust as independent variables significantly influence the purchase decision. Word of Mouth as quasi moderator variables (located as independent variables and moderating variables) significantly influence the purchase decision and have a significant effect as a moderating variable on the relationship between the Trust with the purchase decision.